STUDI ELEMEN PEMBENTUK RUANG PADA INTERIOR LIWAN MASJID BESAR AL-MUBAROK NGANJUK - Wibowo, Dymas Alameelas; Badriyah, Siti (TEXTURE Art and Culture Journal, 2024)
Al-Mubarok Great Mosque is one of the mosques in Nganjuk Regency. The mosque was built in 1812 AD by K.R.T. SosroKoesoemo I or KanjengJimat. The facade of the mosque, which was previously characterised by Javanese style, has changed as a result of restoration. To protect its authenticity, the mosque is designated as a cultural heritage, covering the core building including the liwan room (the main room for worship) in the interior. The diversity of Javanese, Hindu-Buddhist and Chinese cultural patterns in the liwan interior design is a unique feature that is interesting to study. The study of Space Forming Elements in the Liwan Interior of Al-Mubarok Great Mosque in Nganjuk Regency is aresearch that aims to find out the design and space forming elements of the liwan interior of this mosque. This research uses an interior design approach. The research method used is descriptive qualitative. The source of research data is the results of interviews from sources, observation, or field studies, as well as documents and archives. Data validity uses data triangulation techniques from various literature sources. This research uses an interactive analysis model, with data presentation in the form of image descriptions or schemes, narratives, and tables to support the narrative. The results of this study present the suitability of the composition of interior elements to the theme and style as well as the details of the elements that form the interior space of the Al-Mubarok Great Mosque liwan which is functional and has aesthetic value according to the rules of interior design.